Brazilian Nursing Team: Quality of Working Life and The Leadership Influence - Rached, Chennyfer Dobbins Abi; Manning, Jennifer; Liberal, Márcia Mello Costa De; RN, Gabriella de Castro Sousa; RN, Herline Domercant; Amaral, Giovanna Micucci Pires (International Journal of Membrane Science and Technology, 2023)
Objective: Analyzing the relation between the nurses-in-chief managerial styles with the Quality of Working Life (QWL). The balance between quality of life and work brings some sub-dimensions between life outside the workplace and work itself. Most of the investigated studies address the impact of work on life and the impact of life on the job. This analysis is important, as it contributes to several aspects, such as, for example, to increase the level of activity or participation. Materials and methods: Cross-sectional, qualitative, explanatory, and descriptive study. The sample was 61 nursing professionals (RNs) who held board positions, heads of department, managers, unit areas coordinators or supervisors, executive boards and/or departments, and 134 Licensed Practical Nurses (LPN) at a hospital with a direct public administration in Brazil. The data collection was based on The Quality of Working Life Questionnaire (QWLQ-brief) and the Scale of Evaluation of the Managerial Style (SEMS) forwarded electronically. Results: The indices considered satisfactory begin from 55 points. The QWLQ-brief average was 46,39% (neutral position), and the physical/health aspects were considered unsatisfactory (mean 44,89%; 44, 13%).Conclusion: The conclusion showed relational possibilities between the Nurse-in-chief managerial style and the perception of the Quality of Working Life. The perception of the neutral life quality and some unsatisfactory sub-dimensions was related to the managerial style based on tasks.